Activating the Mnemonic Learning Model to Enhance Student Motivation in MTs Miftahul Ulum Situbondo - Evi Nurus Suroiyah; A. Samsul Ma’arif; Mu’alim Wijaya; Laili Sholihah (Mantiqu Tayr: Journal of Arabic Language, 2024)
This research focuses on the activation of the Mnemonic Learning model, with the aim of understanding the process of activating the Mnemonic Learning model at MTs Miftahul Ulum. Based on these issues, the researcher is interested in further exploring them in the form of a scholarly thesis. The research objectives include: How does Mnemonic Learning enhance student motivation at MTs Miftahul Ulum Besuki Situbondo and What is the process of activating Mnemonic Learning at MTs Miftahul Ulum Besuki Situbondo. To address these issues, the author employed a qualitative research method, specifically phenomenological research. Data was collected through observations, interviews, and documentation involving various relevant parties related to the research subject. Data analysis involved data reduction, data presentation, and verification. The findings revealed the creation of more active and motivated learning through the use of the Mnemonic Learning model, leading to better understanding of the Arabic language by seventh-grade students at MTs Miftahul Ulum Besuki Situbondo. The author's hope is that the activation of the Mnemonic Learning Model will be able to make students have a high interest in learning Arabic so that they have standardized Arabic language skills.